Through the Black Mirror
XI, 297 p.
Keywords: This edited collection charts the first four seasons of Black Mirror and beyond, providing a rich social, historical and political context for the show. Across the diverse tapestry of its episodes, Black Mirror has both dramatized and deconstructed the shifting cultural and technological coordinates of the era like no other. With each of the nineteen chapters focussing on a single episode of the series, this book provides an in-depth analysis into how the show interrogates our contemporary desires and anxieties, while simultaneously encouraging audiences to contemplate the moral issues raised by each episode. What if we could record and replay our most intimate memories? How far should we go to protect our children? Would we choose to live forever? What does it mean to be human? These are just some of the questions posed byBlack Mirror, and in turn, by this volume. Written by some of the foremost scholars in the field of contemporary film and television studies,Through the Black Mirror explores how Black Mirror has become a cultural barometer of the new millennial decades and questions what its embedded anxieties might tell us. .